Effect of Mutations , Leadership Style and Employee Competence on Employee Performance - Sophan Bayu (Dinasti International Journal of Education Management And Social Science, 2023)
Literature review article on the effect of mutation, leadership style and employee competence on employee performance is a scientific article that aims to build a research hypothesis on the influence of variables to be used in further research , within the scope of Human Resource Management. The method of writing this Literature Review article is the library research method , which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this literature review article are: 1) Mutations affect Employee Performance; 2) Leadership Style influences Employee Performance ; and 3) Employee Competence influences Employee Performance .